BENEFITS OF TECHNOLOGY INTEGRATION IN PEDAGOGICAL SETTINGS - Mexro’zbek Muxtorjon o’g’li Jo’raboyev; Murodullayeva Nozimahon Karim qizi (Web of Journals Publishing, 2024)
The integration of technology in pedagogical settings represents a transformative approach to education, enhancing teaching and learning experiences. Let's explore the benefits and considerations of incorporating technology into educational practices.